2020
DOI: 10.3233/jad-200576
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes Detected by 18F-FDG PET in the Preclinical Stage of Familial Creutzfeldt-Jakob Disease

Abstract: Background: Pathologic processes in Creutzfeldt-Jakob disease (CJD) are not fully understood. Familial CJD (fCJD) gives opportunities to discover pathologic changes in the preclinical stage. Objective: To investigate cerebral glucose metabolism in the preclinical stage via 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) in fCJD. Methods: Seven asymptomatic carriers of G114V mutation and six family members without PRNP mutation from the same fCJD kindred were included, and were followed for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Asymptomatic family members ( n = 13) were recruited from the same kindred [the same participants were reported in our previous FDG-PET study ( Lu et al, 2020 )]. A detailed family tree was published in the report of the FDG-PET and is provided in Supplementary Figure 1 ( Lu et al, 2020 ). In this kindred, nine family members (four males and five females) have passed away due to CJD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Asymptomatic family members ( n = 13) were recruited from the same kindred [the same participants were reported in our previous FDG-PET study ( Lu et al, 2020 )]. A detailed family tree was published in the report of the FDG-PET and is provided in Supplementary Figure 1 ( Lu et al, 2020 ). In this kindred, nine family members (four males and five females) have passed away due to CJD.…”
Section: Resultsmentioning
confidence: 99%
“…An FDG-PET study was previously conducted in the same participants included in this investigation. The FDG-PET study focused on gray matter alterations, and the results suggested hypometabolic changes in the parietal and temporal lobes in the preclinical stage of CJD ( Lu et al, 2020 ). Although there is limited evidence supporting WM changes in non-affected carriers, preclinical gray matter changes in the same participants could suggest the involvement of WM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations